68.0k views
0 votes
Simplify the expression.
-5+i/2i

User IMR
by
7.5k points

1 Answer

6 votes

Answer:


\rm - (11)/(2)

Explanation:


\rm Simplify \: the \: following: \\ \rm \longrightarrow - 5 + (i)/(2) i \\ \\ \rm Combine \: powers. \\ \rm (i * i)/(2) = (i^(1 + 1))/(2): \\ \rm \longrightarrow - 5 + (i^(1 + 1))/(2) \\ \\ \rm 1 + 1 = 2: \\ \rm \longrightarrow - 5 + (i^2)/(2) \\ \\ \rm i^2 = -1: \\ \rm \longrightarrow - 5 + (( - 1))/(2) \\ \\ \rm \longrightarrow - 5 - (1)/(2) \\ \\ \rm Put \: - 5 - (1)/(2) \: over \: the \: common \: denominator \: 2. \\ \rm - 5 - (1)/(2) = (2( - 5))/(2) - (1)/(2) : \\ \rm \longrightarrow ( - 5 * 2)/(2) - (1)/(2) \\ \\ \rm 2 (-5) = -10: \\ \rm \longrightarrow ( - 10)/(2) - (1)/(2) \\ \\ \rm ( - 10)/(2) - (1)/(2) = ( - 10 - 1)/(2) : \\ \rm \longrightarrow ( - 10 - 1)/(2) \\ \\ \rm -10 - 1 = -11: \\ \rm \longrightarrow - (11)/(2)

User Badgerr
by
7.5k points